2021
DOI: 10.1097/md.0000000000025909
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic targets recognition of rectal adenocarcinoma based on transcriptomics

Abstract: Colorectal cancer is currently the third most common cancer around the world. In this study, we chose a bioinformatics analysis method based on network analysis to dig out the pathological mechanism and key prognostic targets of rectal adenocarcinoma (READ). In this study, we downloaded the clinical information data and transcriptome data from the Cancer Genome Atlas database. Differentially expressed genes analysis was used to identify the differential expressed genes in READ. Community discovery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Grove et al (4) quantitatively analyzed the computed tomography(CT) features from two independent cohorts, demonstrating that convexity score and entropy ratio were important prognostic factors for survival analysis, and were negatively correlated with overall survival in non-small cell lung cancer patients. Meanwhile, prognostic prediction based on biomarkers, such as transcriptome data and DNA methylation data, also plays an important role in helping physicians to identify patients with high mortality risk accurately (2,5,6). For example, by using the transcriptome data, Yi et al (5) identified 7 key genes negatively correlated with the survival rate of rectal adenocarcinoma (READ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grove et al (4) quantitatively analyzed the computed tomography(CT) features from two independent cohorts, demonstrating that convexity score and entropy ratio were important prognostic factors for survival analysis, and were negatively correlated with overall survival in non-small cell lung cancer patients. Meanwhile, prognostic prediction based on biomarkers, such as transcriptome data and DNA methylation data, also plays an important role in helping physicians to identify patients with high mortality risk accurately (2,5,6). For example, by using the transcriptome data, Yi et al (5) identified 7 key genes negatively correlated with the survival rate of rectal adenocarcinoma (READ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, by using the transcriptome data, Yi et al. ( 5 ) identified 7 key genes negatively correlated with the survival rate of rectal adenocarcinoma (READ). Yu et al.…”
Section: Introductionmentioning
confidence: 99%